2000
DOI: 10.1592/phco.20.6.593.35155
|View full text |Cite
|
Sign up to set email alerts
|

Waste Generation of Drug Product Samples versus Prescriptions Obtained Through Pharmacy Dispensing

Abstract: Drug samples are often packaged differently from bulk packaging and thus they may contain a disproportionate amount of waste material. Fifteen drug samples were obtained from seven pharmaceutical companies and the packaging materials were weighed after the samples were removed. The waste produced by the samples was determined for a standard amount of drug and compared with the weight of the waste produced when the same quantity of drug was dispensed through a pharmacy. The average weight of the sample package … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…According to the report of Resource Conservation and Recovery Acts and Environmental Protection Agency; hazardous pharmaceutical wastes have been described as “P list”, “U list”, or “chemical” (D‐list) consisting of toxic substances which may frequently dispose into the water bodies to create human health and environmental harmony impairment . In Bangladesh, currently more than 200 pharmaceutical industries are successfully launching their products in the local market with the approximate BDT 76 500 million per year .…”
Section: Introductionmentioning
confidence: 99%
“…According to the report of Resource Conservation and Recovery Acts and Environmental Protection Agency; hazardous pharmaceutical wastes have been described as “P list”, “U list”, or “chemical” (D‐list) consisting of toxic substances which may frequently dispose into the water bodies to create human health and environmental harmony impairment . In Bangladesh, currently more than 200 pharmaceutical industries are successfully launching their products in the local market with the approximate BDT 76 500 million per year .…”
Section: Introductionmentioning
confidence: 99%
“…There are environmental concerns as well. Waste generated from drug samples is estimated to be 5740 metric tons per year [58].…”
Section: The Risks Of Samplesmentioning
confidence: 99%
“…The small sample size creates 5-fold more packaging waste than traditional packaging, generating an estimated 5740 metric tons of waste each year in the United States. 28 Viewing samples as gifts. The American Academy of Dermatology conducted market research in 1978 and found that samples are given to Table II.…”
Section: Costmentioning
confidence: 99%